Heritability of seed yield, 100-seed weight, and days to maturity in high and low soil fertility in common bean - Urrea, Carlos A.; Singh, S.P. (1989)
A field trial was carried out in CIAT-Quilichao (Colombia) to determine seed yield heritability, wt. of 100 seeds and days to maturity, in soils with high and low levels of fertilization. Plots were fertilized with 600 and 1800 kg of compost (15-15-15)/ha. The F2 and F3 generations of 22 single crossings were evaluated in a random block design with 3 replications. Narrow sense heritability was calculated by regressions of the F3 in the F2. Crossings with the highest yield were A 247 x XAN 112, A 295 x XAN 112, and Catu x XAN 40 while A 301 x G 577 and Ojo de Cabra 24 MU showed the lowest yields. Lower seed yield was observed in F3 in comparison with F2, maybe due to increased homocigosis. Seed yield increased as soil fertility increased. Heritability values for seed yield, days to maturity, and wt. of 100 seeds in high and low fertility soils were 0.57 and 0.61, 0.45 and 0.46, and 0.56 and 0.51, resp. (CIAT)